PENGARUH MOTIVASI BERPRESTASI DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR KKPI SISWA SMK N 1 SURAKARTA - Nashir, Ahmad; Sutaryadi, Sutaryadi; Subarno, Anton (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
Abstract: The objectives of this research are to investigate: (1) the effect of the motivation to achive on the learning achievement; (2) the effect of the learning facilities on the learning achievement; and (3) the simultaneus effect of the motivation to achive and the learning facilities on the learning achievement. This research used the descriptive quantitative research method. The population of the research was all of the XI class students of the office administration skill program of the state vocational high school 1 of Surakarta in the education and training year 2011/2012 as many as 75 students. The sample of the research consisted of 45 students or 60% out of the total number of population, and they were taken by using proportional random sampling technique. The data of the research were gathered by using questionnaire and documentation. They were then analyzed by using the multipel linear regression technique of analysis. The results of the research are as follows: (1) there is a significant and positive effect of the variable of the motivation to achive (X1) on the learning achievement; (2) there is a significant and positive effect of the variable of the learning facilities (X2) on the learning achievement; and (3) there is a simutaneusly significant and positive effect of the variable of the motivation to achive (X1) and that of the learning facilities (X2) on the learning (Y). The relative contribution of the motivation to achive (X1) on the learning achievement (Y) is 66.65%, and that of the learning facilities (X2) on the learning achievement (Y) is 33.34%. The effective contribution of the motivation to achive (X1) on the learning achievement (Y) is 48.05%, and that of the learning facilities (X2) on the learning achievement (Y) is 24.03%.